Cognitive process development in primary school age children with different types of ontogenesis - Maksimenko M.You; Shal L. (Moscow State University of Psychology and Education, 2017)
Section 2 of the correction course presents tasks for the development and formation of cognitive universal educational activities in children of primary school age: visual perception, motor sphere, spatial representations and language. Authors offer exercise for the development of the following skills and abilities: reading skills, including global reading skill, memory, thought processes, calculation abilities and counting operations. Course of correction1. Part 2. Continuation. Вeginning in No 1 (54), 2017